A hybrid GaN/Ga2O3 structure anchored on carbon cloth as a high-performance electrode of supercapacitors. Issue 44 (26th October 2022) - Hu, Yan-Ling; Wang, Zihan; Yuan, Ronghuo; Xu, Zhihan; Dai, Yan; Wang, Bing; Fu, Yao; Ye, Meidan; Yang, Yun; Zou, Zhimin; Jiang, Chunhai
Abstract : GaN/Ga2 O3 /carbon cloth exhibited high performance as a supercapacitor electrode, with α-Ga2 O3 as an absorption/reaction site for H + and GaN as an electron channel. Abstract : A hybrid structure of GaN/Ga2 O3 microrods was fabricated on carbon cloth (CC) using a hydrothermal process combined with a high-temperature nitridation followed by an air annealing process. By elevating the post-annealing temperature to 500 °C, both electron density ( N D ) and specific capacitance ( C a ) of the composite electrode were significantly enhanced. Symmetric SCs assembled with GaN/CC-500 showed great potential in both 1 M H2 SO4 aqueous solution and a PVA–H2 SO4 gel-like electrolyte. The aqueous symmetric GaN/CC-500 SC exhibited an excellent capacitance (1301.20 mF cm −2, 0.5 mA cm −2 ), high rate capability (75.23% of capacitance retention at 10 mA cm −2 ), outstanding cycling stability (77.27% of capacitance retention after 20 000 cycles, 10 mA cm −2 ), and large energy storage capability (27.53 μW h cm −2 of energy density, 0.10 mW cm −2 of power density). All-solid-state symmetric GaN/CC-500 SC also manifested a high capacitance (1183.35 mF cm −2, 0.5 mA cm −2 ) and good rate capability (53.98% capacitance retention, 10 mA cm −2 ). The high electrochemical performance of the GaN/CC-500 electrode is attributed to the GaN/Ga2 O3 hybrid structure, with α-Ga2 O3 providing absorption/redox active sites on the surface, and the heavily oxygen-doped GaN enabling fast electron transport. The microrods with the GaN/Ga2 O3 hybrid structure as the active material for solid SCs can deliver an energy density of 0.58 W h kg −1 (3.54 mW h cm −3 ) with a power density of 154 W kg −1 (0.94 W cm −3 ). The mechanism identified in this work would be helpful in designing GaN-based energy storage devices with better performances in the future.